Dynamic changes of DNA epigenetic marks in mouse oocytes during natural and accelerated aging. (October 2015) - Qian, Yan; Tu, Jiajie; Tang, Nelson Leung Sang; Kong, Grace Wing Shan; Chung, Jacqueline Pui Wah; Chan, Wai-Yee; Lee, Tin-Lap
Abstract: Aging is a complex time-dependent biological process that takes place in every cell and organ, eventually leading to degenerative changes that affect normal biological functions. In the past decades, the number of older parents has increased significantly. While it is widely recognized that oocyte aging poses higher birth and reproductive risk, the exact molecular mechanisms remain largely elusive. DNA methylation of 5-cytosine (5mC) and histone modifications are among the key epigenetic mechanisms involved in critical developmental processes and have been linked to aging. However, the impact of oocyte aging on DNA demethylation pathways has not been examined. The recent discovery of Ten-Eleven-Translocation (TET) family proteins, thymine DNA glycosylase (TDG) and the demethylation intermediates 5hmC, 5fC and 5caC has provided novel clues to delineate the molecular mechanisms in DNA demethylation. In this study, we examined the cellular level of modified cytosines (5mC, 5hmC, 5fC and 5caC) and Tet/Tdg expression in oocytes obtained from natural and accelerated oocyte aging conditions. Here we show all the DNA demethylation marks are dynamically regulated in both aging conditions, which are associated with Tet3 over-expression and Tdg repression. Such an aberrant expression pattern was more profound in accelerated aging condition. The results suggest that DNA demethylation may be actively involved in oocyte aging and have implications for development of potential drug targets to rejuvenate aging oocytes. This article is part of a Directed Issue entitled: Epigenetics dynamics in development and disease.